Multi-index Experimental Study on the Effects of Antarctic Krill oil on the Immune Function of Mice - Hasson, Ramzi; Harris, Keil; Swift, Cobi (International Journal of Agriculture and Food Sciences Research, 2024)
The aim of this study was to investigate the effects of the contents of immunity-enhancing soft capsules with krill oil as the main active ingredient on the immune function of female ICR mice. Methods: A 30-day continuous gavage experiment was performed by setting different doses of subjects, including high, medium and low dose groups and edible vegetable oil control group. During the experiment, a variety of immunological detection methods including carbon clearance test, delayed-type allergic reaction (DTH) test, antibody-producing cell test (hemolytic plaque number) and serum hemolysin were used to comprehensively evaluate the effect of the test substance on the immune function of mice. Results: In the carbon clearance test, the optical density OD(2min and 10min), liver weight, spleen weight and phagocytic index A of mice in each dose group were significantly higher than those in the control group (P < 0.05), suggesting that the subjects could enhance the phagocytic function of mice. DTH test results showed that the weight ratio of left and right ears of mice in each dose group was increased, but there was a statistical difference compared with the control group (P<0.05), indicating that the subject could improve the delayed allergic reaction in mice. The results of antibody-producing cell assay showed that the amount of hemolytic plaque in each dose was greater than that in the normal control group (P<0.05), indicating that the subject could promote the normal growth of mouse antibody-producing cells. The results of serum hemolysin test also showed that the degree of hemagglutination of mice in each dose group in different dilutions of serum was higher than that in the control group (P < 0.05), further confirming the enhancing effect of the test object on the immune function of mice. Conclusion: The content of immunity-enhancing soft capsule (krill oil, Antarctica) can significantly improve the immune function of ICR female mice, which is manifested as enhanced phagocytosis, promotion of delayed allergic reaction, stimulation of antibody production and increase of serum hemolysin level. As an important line of defense for human health, immunity plays an important role in resisting the invasion of external pathogens and maintaining the stability of the internal environment [1]. In recent years, with the acceleration of the pace of life and changes of eating habits, the problem of low immunity is becoming increasingly prominent. Searching for effective immune enhancers has become a hot topic in research. Antarctic krill oil, as a natural product rich in various bioactive components, has been proved to have significant immunomodulatory effect [2] As of May 2023,200 clean female ICR mice were selected as the research objects. By setting the contents of Antarctic krill oil soft capsules with different doses, the effects of Antarctic soft capsules on the immune function of mice were discussed in depth, and scientific basis was provided for the development and application of Antarctic krill oil as an immune enhancer. In this study, carbon clearance test, delayed allergic reaction (DTH) test, antibody-producing cell test and serum hemolysin test were used to comprehensively evaluate the regulatory effect of Antarctic krill oil on the immune function of mice, which provided strong support for its application in the clinical and health care fields.